Nuovi orizzonti delle università per un mondo più solidale - Versaldi, Giuseppe Card. (Alpha Omega, 2021)
Summary: Following closely the documents and the speeches of Pope Francis in its regard, the author proposes ways of undertaking a wise and courageous renewal of the Catholic university, as required by the missionary transformation of a Church which is out-going. A renewal within a continuity, to meet the new challenges of a world in the midst of a crisis which is both anthropological and socio-environmental, in which we encounter regional catastrophes as much as we do social crises and also financial crises. We need a shift od paradigm, not in the form of a synthesis, but in a spiritual atmosphere of research and of certitude based upon the truths of reason and of faith. In this respect, it will be good to appeal to the solidity (the etymological root of solidarity) which derives from knowing that we are responsible for the fragility of others, as we search for our common destiny. This solidarity must be constructed also within our universities, which must not limit themselves just to discovering new elements of knowledge, but which must also bind themselves together in developing new instruments of action by means of innovatory projects which will be capable of remedying the distortions of a culture which is predominantly individualistic and utilitarian in many parts of the world.